Cross-scale analysis of ecosystem services identified and assessed at local and European level - Dick, Jan; Maes, Joachim; Smith, Rognvald I.; Paracchini, Maria Luisa; Zulian, Grazia (Ecological indicators, 2014)
•We compare two methods for assessing the ecosystem services delivered at the scale of a land management unit in the UK.•Sites were described by 73 local scale indicators and 16 indicators obtained from European scale data.•Multivariate statistics revealed complementarity between methods for describing the sites but the total ecosystem service index was critically dependant on indicators selected. In recent years a consistent number of studies carried out at different spatial scales have proposed options for mapping and integrated assessment of ecosystem services. Examples of cross-scale assessments are limited and open questions remain on the extent to which general assessments are able to capture local phenomena. This study aims at investigating what the relation is between ecosystem services analysis carried out at different spatial scales, and to what extent approaches based on input data at different resolution can be reconciled. In particular, the challenges and limitations involved in attempting holistic assessments of ecosystem services at the level of a management unit in the UK were investigated using two sets of ecosystem service indicators: (i) identified by local land managers and (ii) derived from EU-based spatially explicit data coupled with process-based models. The difference in the ecosystem services estimated for 11 sites of the Environmental Change Network (ECN) by the two methodologies was compared using (i) total ecosystem service index (TESI), (ii) regression analysis of comparable ecosystem service indicators, and (iii) multivariate techniques to determine site comparability. The comparative analysis revealed robust grouping of sites by both methods coupled with weak correlation between the different ecosystem service indicators assessed. This study indicated that both methods characterised the general landscapes in a similar way, but total ecosystem service index was critically dependent on indicators selected.